An Eschatological-Hope-Based Pastoral Counseling Model for Congregants Experiencing Bereavement - Johannes S.P. Rajagukguk; Ricky Lukas; Ferdinand Edu (International Perspectives in Christian Education and Philosophy, 2024)
This conceptual research article develops an eschatological-hope-based pastoral counseling model for congregants experiencing bereavement. Bereavement is not only an affective response to death but also a disruption of meaning, embodied routines, social belonging, and theological imagination. Contemporary grief research has clarified the distinction between normative grief, prolonged grief disorder, complicated spiritual grief, and the heterogeneous trajectories through which bereaved persons adapt. However, pastoral responses in local churches often remain fragmented, oscillating between sympathetic presence, doctrinal explanation, ritual care, and informal advice without an integrated model that is clinically cautious and theologically constructive. This study employs a qualitative constructive literature review, synthesizing bereavement psychology, meaning reconstruction theory, spiritual care research, and Christian eschatological theology. The article proposes the PASTOR model: Presence, Assessment, Story, Scripture, Theological lament, Ongoing communal practice, and referral and review. The main synthesis argues that eschatological hope should not be used to bypass grief but to hold lament, embodied absence, continuing bonds, and future-oriented resurrection hope within a disciplined pastoral process. The model contributes a practical framework for churches seeking to accompany mourners without medicalizing ordinary grief, minimizing suffering, or ignoring cases that require professional mental health referral.